Optimalisasi Kemitraan Pendidikan sebagai Upaya Peningkatan Mutu dan Inovasi Lembaga Pendidikan Islam - Nida Nur Aisyah; Awwal Muzakki Alkautsar; Mulyawan Safwandy Nugraha (JMPI: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to analyze the strategic role of partnerships in improving the quality and innovation of Islamic educational institutions through a literature review. The findings indicate that partnership models involving parents, communities, higher education institutions, and the business sector contribute significantly to strengthening the educational ecosystem. These partnerships enrich the learning process by providing diverse learning resources, experience-based learning opportunities, and technological integration. Additionally, external collaboration enhances teacher competence through needs-based training, academic mentoring, and the development of digital media. Partnerships also encourage the emergence of innovative programs, facility improvement, and institutional competitiveness. Overall, partnerships are proven to be an effective strategy for supporting the quality, professionalism, and sustainability of Islamic educational institutions. Keywords: educational partnerships, learning quality, teacher competence, innovation in Islamic education